Awareness of Organ Transplantation among Health Care Professionals and Medical Students - Ahmad, Zahedul Karim; Kabir, Md Humayun; Mazid, Abdul; Akther, Gulshan Ara; Hossain, Md Nur; Islam, Farzana; Zaman, Parvin Dilara (Ibrahim Medical College Journal, 2010)
This cross sectional study was conducted in different medical college hospitals of Dhaka city during the months of Jan-March 2009. The objective of this study was to find out the awareness level on organ transplantation amongst the teachers, doctors and nurses working in these medical college hospitals and 1st to 5th year students. A structured questionnaire was given to the respondents. The total number of respondents was 462 of which 103 (22.3%) were doctors, 268 (58%) were medical students and 91 (19.7%) were nurses. Among the study group 31.4% knew that there was an organ transplantation law in Bangladesh and 16.5% said that there was no such law whereas 52.2% had no idea whatsoever about the law. Of the respondents 33.8% were willing to donate their organs after death, 41.6% did not want to donate and 24.2% were not sure. This study revealed that there was a lack of understanding regarding the religious views on organ transplantation. Only 37.1% of respondents thought that were was no religious objection to organ transplantation whereas 27.1% felt that there was religious objection while 35.7% were not sure. The study shows that there is significant lack of awareness regarding organ transplantation issues among the health care professionals and medical students in Bangladesh. The dictates of religion on this matter were also not clear to most of the respondents. Ibrahim Med. Coll. J. 2009; 3(2): 55-58 Keywords: Organ transplantation, awareness, healthcare professionals, religious sanctions. DOI: 10.3329/imcj.v3i2.4217